Михайло Рудницький і Наукове товариство імені Шевченка: до історії академічних і неакадемічних стосунків - Когут, С. (Слово і Час, 2020)
У статті досліджено довголітню непросту історію стосунків українського літературознавця, критика, журналіста, письменника Михайла Рудницького з Науковим товариством ім. Шевченка у Львові,
зокрема, з окремими членами Філологічної секції Товариства. Ці стосунки переросли у тривале полемічне протистояння, зумовлене різним
розумінням завдань гуманітаристики. Ідеться про дебати в Галичині навколо т. зв. скрипниківського правопису, про історію створення
Української загальної енциклопедії. Уперше публікуються два листи
М. Рудницького до тогочасного заступника голови НТШ В. Левицького. The paper highlights the relationship between the Ukrainian literary critic, journalist, and writer Mykhailo Rudnytskyi and the Shevchenko Scientific Society in Lviv, namely the members of its Philological department. The continuous opposition in these relations was rooted in a different understanding of tasks that might be considered as proper for humanities. In particular, the paper analyses the reasons that prompted М. Rudnytskyi to negatively assess К. Studynskyi’s activity in language and orthographic issues. Rudnytskyi considered the language politics of К. Studynskyi to be amateurish, out-of-date, and incongruous with the contemporary academic requirements and public level of Society. The paper also deals with a theme of debates in Halychyna around Skrypnyk’s orthography of 1929 and the active voice of Mykhailo Rudnytskyi on this issue. Another subject of the paper is the history of the Ukrainian General Encyclopaedia (1930—1933). Th e scholar contributed to this project as one of the editors. Here the paper focuses on Mykhailo Rudnytskyi’s views concerning the Encyclopedic area in particular and the state of Ukrainian academic studies on the whole, as well as the prospects of their development. Th e paper’s author aims to clarify the position of the scholar regarding the classic ‘canon’ of literature and methodology of criticism and evaluation. Despite different opinions and confrontation, in 1935 M. Rudnytskyj became a member of the Philological Section of the Shevchenko Scientific Society. Two letters of Mykhailo Rudnytskyi to the vice-chairman of Shevchenko Scientific Society Volodymyr Levytskyi are published for the first time.